Primary research on unrelated double umbilical cord blood transplantation and implantation kinetics. (1st September 2013) - Song, Kaidi; Sun, Zimin; Liu, Huilan; Geng, Liangquan; Ding, Kaiyang; Wang, Xingbing; Tang, Baolin; Tong, Juan; Yao, Wen; Zhang, Xuhan; Wang, Zuyi
Abstract : Objective: This study sought to examine implantation and implantation kinetics in double umbilical cord blood transplantation (DUCBT). Methods: Twenty-nine patients who underwent a two-unit unrelated donor cord blood transplantation were included in this study. After transplantation, hematopoietic chimerism of the peripheral blood was evaluated based on the results of short tandem repeat polymerase chain reaction. Using these results, we were able to judge whether the transplanted cells implanted, determine which donor's cells implanted, and further examine the kinetics of implantation in DUCBT. The numbers of total nucleated cells (TNCs), CD34 + cells, colony forming units (CFUs), colony forming unit-granulocytes and macrophages (CFU-GMs), and CD3 + cells were compared between the dominant units and the non-dominant units in an attempt to understand the discipline and implantation kinetics of DUCBT. Results: Neither the TNC counts nor the counts of CD34 + cells, CFU, CFU-GM, or CD3 + cells were significantly different between the dominant units and the non-dominant units ( P values of 0.584, 0.322, 0.842, 0.534, and 0.082, respectively). Conclusions: We were able to determine the engraftment status at 14 days after DUCBT, although the implantation kinetics of DUCBT remain uncharacterized and require further research.